2016
DOI: 10.5543/tkda.2015.32754
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and three-year follow-up of patients with isolated myocardial bridge in the mid-Black Sea region: a retrospective single-center study

Abstract: Objective: Myocardial bridge (MB), also known as muscular bridge, is a rare congenital disease with relatively good prognosis. However, it has been associated with unstable angina, myocardial infarction, and sudden cardiac death. Incidence and prognosis of patients diagnosed with isolated MB after having undergone coronary angiography are evaluated in the present retrospective study. Methods: Coronary angiograms of 18,250 patients, obtained between 2008 and 2011, were reexamined for presence of MB at the cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…By analyzing their references, we found another 16 potentially relevant articles that were also downloaded. From the 203 articles, 120 were included in the final analysis of prevalence. Details about search synthesis are presented in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…By analyzing their references, we found another 16 potentially relevant articles that were also downloaded. From the 203 articles, 120 were included in the final analysis of prevalence. Details about search synthesis are presented in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Aksan et al . demonstrated that subjects with MB have a significantly increased QTd during peak exercise compared with its baseline value (42.6 ms versus 36.4 ms), while in non-MB subjects the increase during peak exercise was not statistically significant (29.1 ms, versus a baseline value of 27.1 ms) 72 .…”
Section: Discussionmentioning
confidence: 87%
“…Although generally benign, MB has been associated with coronary spasm, myocardial infarction, unstable angina, supraventricular and ventricular arrhythmia, syncope, myocardial stunning, 7 ventricular septal rupture, 8 transient ventricular dysfunction, or sudden cardiac arrest or death. 9…”
Section: Discussionmentioning
confidence: 99%